2018
DOI: 10.1039/c7nr08892b
|View full text |Cite
|
Sign up to set email alerts
|

Size and surface controllable metal–organic frameworks (MOFs) for fluorescence imaging and cancer therapy

Abstract: Benefiting from their porous structures, metal-organic frameworks (MOFs) have attracted intensive attention for use in drug release. However, the controllable synthesis of MOFs with proper particle sizes is still very challenging, which largely limits its applications. Here, UIO-66-NH2 with controlled particle sizes in the range of 20-200 nm has been achieved successfully. The amine on UIO-66-NH2 is demonstrated for the feasible post-modifying of UIO-66-NH2 to obtain multifunctional MOFs, overcoming the limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 37 publications
1
80
0
Order By: Relevance
“…The anticancer activity was assessed using HepG2 cells, in which incubation with 5-FU@UiO-66-NH 2 -5-FAM-FA had a slightly lesser effect than the same mass of the free drug (cell proliferation 57% vs 40%, respectively, at a concentration of 0.2 mgmL -1 ) despite the targeting effect. This is likely due to the maximum 5-FU loading being reported as 26% w/w for UiO-66-NH 2 , although no loading value for 5-FU@UiO-66-NH 2 -5-FAM-FA is given in the paper[94].The potential of Zr-fum as a delivery vector for biomolecules was investigated by attaching various pro-apoptotic peptides (Bak, Bad, KLK) and a cytochrome c protein (CytC) which, due to their membrane impermeability, are not able to efficiently cross the cell membrane by themselves, to the NMOF surface using His-tags[85]. The authors observed a 20-fold increase in the mean cell internal fluorescence of HeLa cells when incubated with Zr-fum-H 6 CF (H 6 CF = carboxyfluorescein with six histidine residues) and a 30-fold increase for Zrfum-H 6 GFP (H 6 GFP = green fluorescent protein modified with six histidine residues) compared to when cells were incubated with solutions of the same concentration of the respective free peptides in growth media, highlighting the efficiency of Zr-fum in internalising biomolecules not able to do so efficiently themselves.…”
mentioning
confidence: 91%
“…The anticancer activity was assessed using HepG2 cells, in which incubation with 5-FU@UiO-66-NH 2 -5-FAM-FA had a slightly lesser effect than the same mass of the free drug (cell proliferation 57% vs 40%, respectively, at a concentration of 0.2 mgmL -1 ) despite the targeting effect. This is likely due to the maximum 5-FU loading being reported as 26% w/w for UiO-66-NH 2 , although no loading value for 5-FU@UiO-66-NH 2 -5-FAM-FA is given in the paper[94].The potential of Zr-fum as a delivery vector for biomolecules was investigated by attaching various pro-apoptotic peptides (Bak, Bad, KLK) and a cytochrome c protein (CytC) which, due to their membrane impermeability, are not able to efficiently cross the cell membrane by themselves, to the NMOF surface using His-tags[85]. The authors observed a 20-fold increase in the mean cell internal fluorescence of HeLa cells when incubated with Zr-fum-H 6 CF (H 6 CF = carboxyfluorescein with six histidine residues) and a 30-fold increase for Zrfum-H 6 GFP (H 6 GFP = green fluorescent protein modified with six histidine residues) compared to when cells were incubated with solutions of the same concentration of the respective free peptides in growth media, highlighting the efficiency of Zr-fum in internalising biomolecules not able to do so efficiently themselves.…”
mentioning
confidence: 91%
“…They concluded that the lower the concentration of the reactants, the larger the particle size of Fe-MIL-53-NH 2 . Additionally, Gao et al studied the effects of benzoic acid on the particle size of UIO-66-NH 2 and synthesized it by a hydrothermal method [38]. Unlike the above, the lower the benzoic acid, the smaller the particle size.…”
Section: Particle Size Control To Achieve Functional Transfer Of Mofsmentioning
confidence: 99%
“…Compared with other MOF-based drug carriers, UiO-66-NH 2 has a high degree of connectivity of the metal clusters in the crystal structure, generating exceptional mechanical stability and chemical stability in a broad range of pH values. In addition, the amino group on the UIO-66-NH 2 opens up the possibility of post-modification of UiO-66-NH 2 with multiple properties [64][65][66][67][68]. Meanwhile, polysilsesquioxanes (PSQs), an organosilica with organic/inorganic hybrid structure, have high stability, biocompatibility, and easy functionalization [40,48].…”
Section: Stability Testmentioning
confidence: 99%